The Expression of Nominal Possession in the Spanish Spoken in the Colombian Eastern Plains - Bejarano Bejarano, Daniel Eduardo (2026)
This article examines the trends, distribution, and frequency of possessive adjectives (e.g., su casa), possessive periphrasis (e.g., la casa suya), and prepositional constructions introduced by de (e.g., la casa de él/ella) as variants for expressing nominal possession in the Spanish of the Colombian Orinoquía region (Casanare, Meta, and Vichada). Based on a corpus of field interviews, frequency maps were created to reveal both the existence of the variants and their usage distribution. The findings confirmed speakers' preference for adjectival forms, followed by periphrasis and prepositional forms, the latter being more frequent in second and third person contexts, particularly in third person as a strategy to disambiguate su or suyo. Statistical analyses demonstrated the influence of various sociolinguistic factors, such as gender, education, and place of upbringing, on the use of these variants. This pioneering study contributes to the understanding of Spanish morphosyntax in a little-explored geographical region, thereby broadening the perspective on linguistic varieties in Colombia.